The Effect of financial compensation and career development on employee retention with non-physical work environments as moderating variables - Nopriella Permatasari; Mega Asri Zona (Universitas Negeri Padang, 2021)
This study aims to analyze: (1) the effect of financial compensation on employee retention (2) the effect of career development on employee retention (3) the influence of the non-physical work environment which moderates the effect of financial compensation on employee retention (4) the influence of non-physical work environments that moderate the effect of career development on employee retention. This research is a causal research. The population in this study were all non-managerial employees of Bank Bengkulu Cabang Curup and Bank Bengkulu Cabang Pembenatu Pasar Tengah, with a total of 38 people. The sampling technique was taken using total sampling where the number of samples was the same as the population, namely 38 people. Collecting data using a questionnaire with a Likert scale. The analysis technique used is through the SPSS 20.0 software. The results of data processing in this study indicate that: (1) Financial compensation has a positive and significant effect on employee retention at Bank Bengkulu Cabang Curup dan Bank Bengkulu Cabang Pembantu Pasar Tengah, (2) Career development has a positive and significant effect on employee retention at Bank Bengkulu Cabang Curup dan Bank Bengkulu Cabang Pembantu Pasar Tengah, (3) non-physical work environment does not significantly moderate the effect of financial compensation on employee retention at Bank Bengkulu Cabang Curup dan Bank Bengkulu Cabang Pembantu Pasar Tengah, (4) non-physical work environment does not significantly moderate the effect of career development on employee retention at Bank Bengkulu Cabang Curup dan Bank Bengkulu Cabang Pembantu Pasar Tengah.